Beaded phenolic resin as well as preparation method and application thereof
By preparing beaded phenolic resin in a bubble reactor and regulating the polycondensation reaction process using the Tindal effect, the problem of difficult crushing of existing phenolic resins is solved, and the beaded phenolic resin with high monodispersion is achieved, which improves its performance in the field of new energy batteries.
Patent Information
- Application Number
- CN202510001512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
Due to the high hardness and difficulty in crushing of existing phenolic resins, it is difficult to develop powder-shaped microbead-type materials.
By preparing beaded phenolic resin in a bubble reactor, the polycondensation reaction process is regulated by using the Tindal effect to control the monodispersion of the particle size, and the preparation of beaded phenolic resin with high monodispersion is achieved.
The high monodispersion of beaded phenolic resin has been achieved, which has improved its first efficiency and energy density in the field of new energy batteries, and simplified the process flow.
Smart Images

Figure CN119798575A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a beaded phenolic resin and a preparation method and application thereof. Background Art
[0002] Based on the needs of energy security and reducing greenhouse gas emissions, since 2009, the state has subsidized and encouraged the development of new energy industries such as power battery vehicles. In 2022, domestic new energy vehicle sales will reach 25.6% of the market share (statistics from the China Automobile Association). The rapid growth in new energy vehicle sales is inseparable from the continuous development of battery material technology, including the efficient iteration and progress of positive, negative, diaphragm, electrolyte and other materials. For battery negative electrode materials, the scientific research community has developed four major categories: alloy materials, metal oxide and sulfide materials, organic materials and carbon-based materials. Among them, amorphous carbon materials in carbon-based materials are most likely to be commercialized.
[0003] Hard carbon is the most commonly used carbon-based material, which is made by high-temperature calcination and carbonization of biomass materials (such as coconut shells, glucose, sucrose, cellulose, lignin), asphalt, coal, phenolic resin, etc. Among them, phenolic resin is the most common negative electrode material after carbonization.
[0004] Conventional phenolic resin is in block form and needs to be crushed before carbonization. The resulting hard carbon is used as a new energy electrode material. It is far superior to the uncrushed block resin in terms of energy density and first coulombic efficiency. However, phenolic resin is very hard and extremely difficult to crush.
[0005] Therefore, there is an urgent need for powdered micro-bead phenolic resin in the art. Summary of the invention
[0006] In view of this, the present invention provides a beaded phenolic resin and a preparation method thereof. The beaded phenolic resin has high monodispersity, (D90-D10) / D50=1.1-2, and can be applied to activated carbon, carbon molecular sieves, fuel cells, new energy batteries, capacitors, supercapacitors, rubber products and other fields.
[0007] The bead-shaped phenolic resin of the present invention is used as a negative electrode raw material prepared by carbonization of a precursor and is applied in the field of new energy batteries, and has excellent performances such as initial efficiency and energy density.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] On one hand, the present invention provides a beaded phenolic resin, which is a phenolic resin polymer. The monodispersity of the beaded phenolic resin particles is (D90-D10) / D50=1.1-2, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc.
[0010] In one embodiment, the beaded phenolic resin has a molecular weight between 800 and 1,000,000, for example, 800, 1,000, 5,000, 10,000, 50,000, 100,000, 300,000, 500,000, 800,000, 1,000,000, and the like.
[0011] The monodispersity of particles refers to the uniformity of the particle size, which is usually measured by (D90-D10) / D50. The smaller the ratio, the better the uniformity and the higher the monodispersity.
[0012] In one embodiment, the beaded phenolic resin is prepared from a phenolic compound and an aldehyde compound in a bubbling reactor.
[0013] Another aspect of the present invention provides a method for preparing the bead-shaped phenolic resin, which can be prepared from conventional raw materials such as phenolic compounds, aldehyde compounds and auxiliary agents through a polycondensation reaction.
[0014] In the method of the present invention, the progress of the polycondensation reaction is identified by the Tyndall effect. When the transparency of the polycondensation reaction system shows the Tyndall phenomenon (that is, when a beam of light passes through the colloid, a bright "pathway" can be observed in the colloid), the polymerization reaction conditions are regulated to control the particle size monodispersity of the polymer microspheres in the system within the desired range, thereby obtaining the beaded phenolic resin product.
[0015] Specifically, a method for preparing a beaded phenolic resin is carried out in a bubbling reactor, and the steps include:
[0016] S1: mixing a phenolic compound, an aldehyde compound, an emulsifier, a stabilizer, a porogen and a solvent, and heating the mixture under stirring to perform a polycondensation reaction;
[0017] S2: When the reaction reaches the point where the Tyndall phenomenon occurs in the system, the reaction temperature is kept constant, ammonia is introduced, an anticoagulant is added, and the stirring speed is reduced to carry out a reverse phase polymerization reaction;
[0018] S3: When the system becomes turbid after the reaction, the stirring speed of step S1 is restored, and the introduction of ammonia is stopped, and the temperature is raised to the target temperature to obtain a slurry containing the bead-like phenolic resin.
[0019] In the preparation method of the present invention, the preparation of the beaded phenolic resin is carried out in a bubbling reactor. On the one hand, bubbling can provide sufficient disturbance for the reaction liquid in the kettle to make the system uniform during the reaction process; on the other hand, compared with stirring with a stirring paddle, the beaded resin balls formed by bubbling disturbance are less aggregated and have better particle size uniformity.
[0020] In one embodiment, the phenolic compound in step S1 includes at least one of phenol, cresol, xylenol, resorcinol, phloroglucinol, 3-aminophenol, tert-butylphenol and bisphenol A.
[0021] In one embodiment, the aldehyde compound in step S1 includes at least one of formaldehyde, acetaldehyde, paraformaldehyde, terephthalaldehyde and furfural.
[0022] In one embodiment, the solvent in step S1 is at least one of acetonitrile, water, methanol, anhydrous ethanol and isopropanol.
[0023] In one embodiment, the molar ratio of the aldehyde compound to the phenolic compound in step S1 is 0.5-10:1, for example 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.
[0024] In one embodiment, the amount of the solvent in step S1 is 1-5 times the total weight of the phenolic compound and the aldehyde compound, for example, 1 time, 2 times, 3 times, 4 times, 5 times, etc.
[0025] In one embodiment, an emulsifier, a stabilizer and a porogen are added to the polycondensation reaction system in step S1 at the same time; all of them are conventional additives in the field and can be selected conventionally, specifically:
[0026] Wherein, the emulsifier includes at least one of polyoxyethylene stearate, monolauric acid glycerol, alkoxylated fatty alcohol, polyoxyethylene ether, polymer of propylene oxide and ethylene oxide, and hexadecyltrimethylammonium bromide;
[0027] Preferably, the amount of the emulsifier added is 1-10wt% of the total weight of the phenolic compound and the aldehyde compound, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc.;
[0028] Wherein, the stabilizer comprises at least one of polyvinyl pyrrolidone, methyl silicone oil, polyvinyl alcohol, sodium dodecyl sulfonate, styrene and olefin copolymer, sodium octadecyl sulfonate, polyethylene glycol, methyl cellulose, carboxymethyl cellulose, starch modification, and chitosan modification;
[0029] Preferably, the stabilizer is added in an amount of 2-6 wt% of the total weight of the phenolic compound and the aldehyde compound, such as 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, etc.;
[0030] Wherein, the porogen includes at least one of Pluronic F127, P123 (polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer), and PEG6000;
[0031] The amount of the porogen added is 1-3wt% of the total weight of the phenolic compound and the aldehyde compound, for example, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt% and the like.
[0032] In one embodiment, a catalyst is further added to the polycondensation reaction system in step S1;
[0033] The catalyst comprises at least one of p-toluenesulfonic acid, phosphoric acid, oxalic acid, urotropine, ammonia, ammonia water, diethanolamine, triethanolamine, methylamine, acetamine, p-phenylenediamine, ethylenediamine, triethylamine, sodium hydroxide and hydrochloric acid;
[0034] The added amount of the catalyst is 1-10wt% of the total weight of the phenolic compounds and the aldehyde compounds, for example 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% and the like.
[0035] In one embodiment, the stirring speed in step S1 is 50-500rpm / min, for example, 50rpm / min, 100rpm / min, 150rpm / min, 200rpm / min, 250rpm / min, 300rpm / min, 350rpm / min, 400rpm / min, 450rpm / min, 500rpm / min, etc.
[0036] In one embodiment, the polycondensation reaction in step S1 is carried out at a temperature of 40-300°C, such as 40°C, 60°C, 100°C, 150°C, 200°C, 250°C, 300°C, etc.;
[0037] It should be noted that in the preparation method of the present invention, the transparency of step S2 shows the Tyndall phenomenon, which means that when a beam of light passes through the reaction liquid, a bright "pathway" can be observed in the reaction liquid; in specific implementation, one of the methods is to use a flashlight to illuminate the reaction liquid in the sight glass of the reactor, and when the clear and transparent liquid turns into a milky white light column, this can be determined as the time when the transparency of the reaction system of step S1 of the present invention shows the Tyndall phenomenon.
[0038] In one embodiment, in the process of introducing ammonia gas in step S2, the ammonia flow rate is 50-800 ml / min, for example, 50 ml / min, 100 ml / min, 200 ml / min, 300 ml / min, 400 ml / min, 500 ml / min, 600 ml / min, 700 ml / min, 800 ml / min, etc.;
[0039] In one embodiment, the anticoagulant in step S2 is paraflow (an oily substance formed by condensation of alkylnaphthalene, chlorinated paraffin and naphthalene);
[0040] Preferably, the anticoagulant is added in an amount of 1-10wt% of the total weight of phenolic compounds and aldehyde compounds, for example 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% and the like.
[0041] In one embodiment, the stirring speed is reduced in step S2 to 10-70% of the stirring speed in step S1, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, etc.
[0042] In one embodiment, the reverse phase polymerization reaction in step S2 is carried out at a reaction temperature at which the Tyndall phenomenon occurs, and the reaction is carried out while maintaining the temperature constant.
[0043] It should be noted that, in the preparation method of the present invention, the reaction in step S3 until the system becomes turbid refers to the state when the Tyndall phenomenon disappears (that is, when a beam of light passes through the reaction liquid, it is observed that there is no bright "pathway" in the reaction liquid). In specific implementation, one method is to use a flashlight to illuminate the reaction liquid in the sight glass. When it turns into a turbid and opaque state, it can be determined that the reaction system in step S3 of the present invention becomes turbid, that is, the time when the Tyndall phenomenon disappears.
[0044] In one embodiment, the temperature is raised to a target temperature in step S3, and there is no specific requirement on the heating rate. The target temperature is above 40°C, preferably 40-300°C, for example 40°C, 60°C, 100°C, 150°C, 200°C, 250°C, 300°C, etc.
[0045] In the preparation method of the present invention, the slurry containing the bead-shaped phenolic resin is obtained in step S3. In actual production, the powder of the bead-shaped phenolic resin can be obtained by conventional post-treatment methods such as filtering and drying.
[0046] Another aspect of the present invention provides the use of the bead-shaped phenolic resin described above.
[0047] The bead-shaped phenolic resin of the present invention can be applied to the fields of activated carbon, carbon molecular sieves, fuel cells, new energy batteries, capacitors, supercapacitors, rubber products, etc.
[0048] In one embodiment, the beaded phenolic resin can be applied to a sodium ion battery, specifically, the beaded phenolic resin is used as a precursor and subjected to a high temperature carbonization treatment to prepare a negative electrode material for a sodium ion battery;
[0049] Wherein, the high-temperature carbonization treatment is carried out in an inert protective gas atmosphere such as nitrogen; the carbonization temperature is 600-1600°C, for example, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, etc., and the carbonization time is 0.5-8h, for example, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, etc.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] (1) The bead-shaped phenolic resin of the present invention has high monodispersity and is applied in the field of new energy batteries, with high initial efficiency and high energy density.
[0052] (2) The preparation method of the present invention has a simple process. The monodispersity of the resin can be improved by performing two-step regulation on the reaction system during the Tyndall effect period, i.e., first performing the operation of "passing ammonia gas + adding an anticoagulant + reducing the rotation speed", and then restoring the rotation speed after the reaction system becomes turbid.
[0053] (3) The present invention uses a bubbling reactor instead of a common mechanical stirring kettle to prepare the beaded resin, further improving the monodispersity, and ultimately controlling the monodispersity of the resin to be between (D90-D10) / D50=1.1 and 2, thereby greatly improving the particle uniformity of the beaded resin powder product. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a microscope photo of the beaded phenolic resin prepared in Example 1;
[0055] Figure 2 The monodispersity curve of the beaded phenolic resin prepared in Example 1;
[0056] Figure 3 The monodispersity curve of the beaded phenolic resin prepared in Comparative Example 1;
[0057] Figure 4 This is the monodispersity curve of the bead-shaped phenolic resin prepared in Comparative Example 2. DETAILED DESCRIPTION
[0058] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0059] The following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.
[0060] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially.
[0061] In each embodiment and comparative example of the present invention, the sources of the main raw materials used are as follows:
[0062] Formaldehyde solution: 37-40wt%, Beijing Inokai Technology Co., Ltd.
[0063] Phenol: 99wt%, Beijing Inokai Technology Co., Ltd.
[0064] paraflow (alkyl naphthalene): ≥60%, Guangdong Wengjiang Chemical Reagent Co., Ltd.
[0065] The main analytical methods used in the examples and comparative examples of the present invention are as follows:
[0066] Observation of beaded resin morphology: The beaded resin was observed using a Keyence VHX-7000 microscope with a magnification of 600-1000 times.
[0067] Monodispersity Determination: Malvern Mastersizer 3000 laser particle size analyzer was used to determine the monodispersity of the bead resin.
[0068] Molecular weight determination: Agilent 1260 gel chromatography was used in accordance with GB / T 36214.1-2018 Plastics size exclusion chromatography for determination of average molecular weight and molecular weight distribution of polymers.
[0069] Example 1
[0070] (1) Preparation of beaded phenolic resin
[0071] 94g (1mol) phenol, 162g (2mol) 37% formaldehyde solution, 384g 20wt% isopropanol aqueous solution, 12.8g p-toluenesulfonic acid, 12.8g lauric acid monoglyceride, 10.2g methyl silicone oil, 5.1g PEG6000 were kept at 22°C for 3 hours, then added to a bubbling reactor for mixing, and heated to 200°C for polycondensation at a stirring speed of 300rpm / min. When the reaction solution showed the Tyndall phenomenon, the following operations were performed: the reaction temperature was kept constant at this moment, the speed was halved, ammonia (flow rate 500ml / min) was introduced, 12.8g paraflow was added, and the reaction was carried out at a constant temperature until the system became turbid, and then the original speed was restored and the nitrogen was stopped. The reaction was continued to be heated to 200°C, the reaction was completed, and a beaded phenolic resin slurry was obtained after natural cooling.
[0072] The morphology of phenolic resin particles in the slurry was observed under a microscope. Figure 1 The monodispersity was tested by laser particle size analyzer. The monodispersity and curve are shown in Table 1. Figure 2 ; The molecular weight was determined by GPC to be 3.85×10 4 .
[0073] (2) Preparation of bead-shaped resin-based carbonized materials
[0074] The beaded resin slurry obtained in step (1) was filtered and dried to obtain a solid powder, which was carbonized in a box furnace (SG-XL, Shanghai Institute of Optics and Precision Mechanics, Chinese Academy of Sciences) at a carbonization temperature of 1200° C. for 2 hours to obtain a carbonized material.
[0075] (3) Application of carbonized materials as electrode materials in sodium ion batteries
[0076] Using the metal sodium sheet as the negative electrode and the carbonized material obtained in step (4) as the negative electrode, a button cell was assembled in an argon-protected glove box. The cell was charged and discharged at a current density of 0.1 C at a voltage of 0-1.5 V for two cycles. The reversible capacity and the first coulombic efficiency (discharge process) were measured. The results are shown in Table 1.
[0077] Example 2
[0078] (1) Preparation of beaded phenolic resin
[0079] 150g (1.6mol) phenol, 77g (0.8mol) 31% formaldehyde solution, 1139g 10wt% acetonitrile aqueous solution, 2.3g urotropine, 22.8g stearic acid polyoxyethylene ester, 13.7g polyvinyl pyrrolidone, 6.8g Pluronic F127 were kept at a constant temperature of 22°C for 3 hours, then added to a bubbling reactor for mixing, and heated to 40°C for polycondensation at a stirring speed of 50rpm / min. When the reaction solution showed the Tyndall phenomenon, the following operations were performed: the reaction temperature was kept constant at this moment, the speed was reduced to 10% of the original speed, ammonia (flow rate 800ml / min) was introduced, 22.8g paraflow was added, and the system was kept at a constant temperature until it became turbid, and then the original speed was restored and the nitrogen was stopped. The temperature was continued to be raised to 40°C, the reaction was terminated, and a beaded phenolic resin slurry was obtained after natural cooling. The molecular weight was 3.5×10 4 .
[0080] The monodispersity and electrical conductivity of the beaded phenolic resin of this embodiment were tested in the same manner as steps (2) and (3) of Example 1. The test results are shown in Table 1.
[0081] Example 3
[0082] (1) Preparation of beaded phenolic resin
[0083] 28g (0.3mol) phenol, 243g (3mol) 37% formaldehyde solution, 271g 6wt% methanol aqueous solution, 27.1g triethanolamine, 2.7g hexadecyltrimethylammonium bromide, 5.4g methylcellulose, 2.7g P123 were kept at 22°C for 3 hours, then added to a bubbling reactor for mixing, heated to 300°C at a stirring speed of 500rpm / min for polycondensation reaction, and when the reaction solution showed Tyndall phenomenon, the following operations were performed: the reaction temperature was kept constant at this moment, the speed was reduced to 70% of the original speed, ammonia was introduced (flow rate 50ml / min), 2.7g paraflow was added, and the reaction was kept at a constant temperature until the system became turbid, and then the original speed was restored and the nitrogen was stopped. The temperature was continued to be raised to 300°C, the reaction was terminated, and the bead-shaped phenolic resin slurry was obtained after natural cooling. The molecular weight was 3.1×10 4 .
[0084] The monodispersity and electrical conductivity of the beaded phenolic resin of this embodiment were tested in the same manner as steps (2) and (3) of Example 1. The test results are shown in Table 1.
[0085] Comparative Example 1
[0086] The method of Example 1 was used to prepare beaded phenolic resin, except that in step (1), when the transparency of the system showed the Tyndall phenomenon, ammonia was not introduced. The other operations were the same as those of Example 1. The results of the monodispersity and the charge-discharge test are shown in Table 1, and the monodispersity curve is shown in Table 1. Figure 3 .
[0087] Comparative Example 2
[0088] The method of Example 1 was used to prepare beaded phenolic resin, except that step (1) was carried out in a mechanical stirring kettle without a bubbling function. The resin monodispersity and buckling test results of this group of samples are shown in Table 1, and the monodispersity curve is shown in Figure 4 .
[0089] Comparative Example 3
[0090] The beaded phenolic resin was prepared by the method of Example 1, except that in step (1), when the transparency of the system showed the Tyndall phenomenon, no anticoagulant was added. The other operations were the same as in Example 1. The monodispersity and charge-discharge test results are shown in Table 1.
[0091] Comparative Example 4
[0092] The method of Example 1 was used to prepare beaded phenolic resin, except that in step (1), when the transparency of the system showed Tyndall phenomenon, the stirring speed was not reduced. Other operations were the same as in Example 1. The monodispersity and charge-discharge test results are shown in Table 1.
[0093] Comparative Example 5
[0094] The method of Example 1 was used to prepare beaded phenolic resin, except that in step (1), after the system became turbid, the reaction was immediately stopped to obtain the product. The other operations were the same as those of Example 1. The product was a colloidal agglomerate and no resin beads were formed.
[0095] Table 1
[0096]
[0097] The smaller (D90-D10) / D50 is, the higher the monodispersity of the particle size is. By comparing Example 1 and Comparative Example 1 in Table 1, combined with Figure 1 , 2 and Figure 3 It can be seen that compared with Comparative Example 1 in which ammonia gas was not introduced during the Tyndall effect stage, the monodispersity of Example 1 is greatly improved, and the battery material prepared after carbonization is superior to Comparative Example 1 in both reversible capacity and first coulombic efficiency.
[0098] Comparative Example 2 in Table 1 uses a mechanical stirring kettle, compared to Example 1 which uses a bubbling reactor. The prepared beaded resin has a monodispersity (combined Figure 4) or battery performance, they are far behind Example 1.
[0099] Similarly, the monodispersity and battery performance of Comparative Examples 3 and 4, which performed corresponding regulation operations in the Tyndall effect stage, also lag far behind those of Example 1.
[0100] In summary, the operation of improving the monodispersity of resin particles adopted in the present invention has significant effects, is applied in the field of new energy battery materials, has excellent charge-discharge performance, and has broad prospects for industry development.
Claims
1. A beaded phenolic resin, characterized in that: The monodispersity of the bead-shaped phenolic resin particles is (D90-D10) / D50=1.1-2.
2. The bead-shaped phenolic resin according to claim 1, characterized in that The molecular weight is 800-1000000.
3. The bead-shaped phenolic resin according to claim 1 or 2, characterized in that: The method is prepared from phenolic compounds and aldehyde compounds in a bubbling reactor.
4. A method for preparing the bead-shaped phenolic resin according to any one of claims 1 to 3, characterized in that: The process is carried out in a bubble reactor, and the steps include: S1: mixing a phenolic compound, an aldehyde compound, an emulsifier, a stabilizer, a porogen and a solvent, and heating the mixture under stirring to perform a polycondensation reaction; S2: When the reaction reaches the point where the Tyndall phenomenon occurs in the system, the reaction temperature is kept constant, ammonia is introduced, an anticoagulant is added, and the stirring speed is reduced to carry out a reverse phase polymerization reaction; S3: When the system becomes turbid after the reaction, the stirring speed of step S1 is restored, and the introduction of ammonia is stopped, and the temperature is raised to the target temperature to obtain a slurry containing the bead-like phenolic resin.
5. The preparation method according to claim 4, characterized in that: The phenolic compound in step S1 includes at least one of phenol, cresol, xylenol, resorcinol, phloroglucinol, 3-aminophenol, tert-butylphenol and bisphenol A; and / or The aldehyde compound in step S1 comprises at least one of formaldehyde, acetaldehyde, paraformaldehyde, terephthalaldehyde and furfural; and / or The solvent in step S1 is at least one of acetonitrile, water, methanol, anhydrous ethanol and isopropanol; and / or The molar ratio of the aldehyde compound to the phenol compound in step S1 is 0.5-10:1; and / or The amount of the solvent used in step S1 is 1-5 times the total weight of the phenolic compound and the aldehyde compound.
6. The preparation method according to claim 4, characterized in that: The emulsifier in step S1 includes at least one of polyoxyethylene stearate, monolaurin, alkoxylated fatty alcohol, polyoxyethylene ether, polymer of propylene oxide and ethylene oxide, and cetyltrimethylammonium bromide; Preferably, the amount of the emulsifier added is 1-10 wt % of the total weight of the phenolic compound and the aldehyde compound; and / or The stabilizer in step S1 includes at least one of polyvinyl pyrrolidone, methyl silicone oil, polyvinyl alcohol, sodium dodecyl sulfate, styrene-alcohol copolymer, sodium octadecyl sulfate, polyethylene glycol, methyl cellulose, carboxymethyl cellulose, starch modification, and chitosan modification; Preferably, the stabilizer is added in an amount of 2-6 wt % of the total weight of the phenolic compound and the aldehyde compound; and / or The porogen in step S1 includes at least one of Pluronic F127, P123, and PEG6000; The added amount of the porogen is 1-3 wt % of the total weight of the phenolic compound and the aldehyde compound.
7. The preparation method according to claim 4, characterized in that: A catalyst is also added to the polycondensation reaction system in step S1; The catalyst comprises at least one of p-toluenesulfonic acid, phosphoric acid, oxalic acid, urotropine, ammonia, ammonia water, diethanolamine, triethanolamine, methylamine, acetamine, p-phenylenediamine, ethylenediamine, triethylamine, sodium hydroxide and hydrochloric acid; Preferably, the catalyst is added in an amount of 1-10 wt % of the total weight of the phenolic compound and the aldehyde compound.
8. The preparation method according to claim 4, characterized in that: The stirring speed in step S1 is 50-500 rpm / min; and / or The polycondensation reaction in step S1 is carried out at a temperature of 40-300°C; and / or In the process of introducing ammonia in step S2, the ammonia flow rate is 50-800 ml / min; and / or The anticoagulant in step S2 is paraflow; Preferably, the anticoagulant is added in an amount of 1-10 wt % of the total weight of the phenolic compound and the aldehyde compound; and / or The step S2 of reducing the stirring speed is to reduce the stirring speed to 10-70% of the stirring speed in step S1; and / or The target temperature in step S3 is above 40°C, preferably 40-300°C.
9. Application of the bead-shaped phenolic resin described in any one of claims 1 to 3 or the bead-shaped phenolic resin prepared by the method described in any one of claims 4 to 8 in the fields of activated carbon, carbon molecular sieve, fuel cell, new energy battery, capacitor, super capacitor, and rubber products.
10. Use of the beaded phenolic resin according to any one of claims 1 to 3 or the beaded phenolic resin prepared by the method according to any one of claims 4 to 8 in a sodium ion battery, characterized in that: The sodium ion battery negative electrode material is prepared by using beaded phenolic resin as a precursor and performing high temperature carbonization treatment; Preferably, the high temperature carbonization treatment is carried out in an inert protective gas atmosphere such as nitrogen; Preferably, the carbonization temperature is 600-1600° C., and the carbonization time is 0.5-8 h.
Citation Information
Patent Citations
Phenol formaldehyde resin carbon micro-sphere preparation method and application of phenol formaldehyde resin carbon micro-sphere in lithium ion battery electrode
CN103545520A
Polycondensation beaded macroporous resin catalyst and preparation method thereof
CN104014368A
Microparticulate composite metal hydroxide, calcined product thereof, method for production thereof, and resin composition thereof
CN109906202A
Preparation method of microspherical phenolic resin
CN115449041A
Resin-based hard carbon microspheres and preparation method thereof
CN118164468A